Patrick Altman : La déposition de l’image - Déry, Louise (CV Photo, 2002)
Abstract Using abundant photographie documentation from various collections, Patrick Altman's personal museum highlights the inventorying and classification systems used by museum collections. He allows generous contact with hundreds of photographs, which he deploys in relation to the exhibition space, while limiting access to it and thus encouraging a fragmented and unstable perception of the images. As a photographer-curator, he is unorthodox in his way of producing and exhibiting, and he paraphrases the methods and manners of museology to exemplify the issues it faces.